The Effects of Sagittal Plane Postures on Trunk Rotation Range of Motion - Montgomery, Trevor (Auckland University of Technology, 2008)
Axial rotation is regarded as an essential movement of the trunk that allows many individuals to participate in vocations, sports and activities of daily living. Unfortunately when the destabilising nature of rotation is combined with that of spinal flexion, the risk of injuring the spine can increase significantly. Few studies have investigated the potential benefits that maximizing trunk rotation has in certain vocation and sport-related arenas and none have looked at whether adopting certain spinal postures in the sagittal plane can maximise trunk rotation more than others. The aim of the study was to determine the effects of alterations of trunk inclination, spinal posture, pelvic fixation and turning direction on the active range of motion (ROM) of trunk rotation. Twenty healthy individuals participated in the main study. Retro-reflective markers were placed on key anatomical locations and used to track the movement of the thorax and pelvis during a series of repeated maximal trunk rotations in ten different spinal positions within the sagittal plane. Trunk kinematics and kinetics were recorded simultaneously using an optoelectronic motion analysis and force platform measuring system. A repeated-measures multiple analysis of variance (MANOVA) was used to test for the main effects of trunk inclination, spinal posture, fixation of pelvis and direction of turn on maximum active ROM of trunk rotation, maximum pelvic rotation and the anterior-posterior and lateral displacement of the centre of pressure (COP). To investigate test-retest reliability, ten participants were tested on two separate days. Repeatability for each outcome measure was investigated using interclass correlation coefficients (ICC) and Bland Altman graphs. The majority of subjects showed reasonable test-retest reliability for trunk rotation measures in each of the test positions, with ICC’s ranging between 0.562 – 0.731. Overall, trunk inclination (0°, 22.5°, 45°) forward in the sagittal plane had a significant effect on trunk and pelvic rotation (p<0.001) and lateral displacement of the COP (p<0.005) during trunk rotation. As trunk inclination increased from 0° to 45° there was an average increase in trunk rotation ROM of approximately 10 % (approximately 3.4°). Furthermore, increasing trunk inclination led to an increase in lateral displacement of the COP and a decrease in pelvic rotation. Spinal posture (neutral, flexed, extended) at a forward inclination of 45° had a significant effect on trunk rotation (p<0.01) and pelvic rotation (p<0.05), with a neutral spine averaging approximately 3 % (approximately 1.1°) more trunk rotation than a flexed or extended posture. The position and posture of the spine in the sagittal plane appears to have a significant influence on ranges of trunk rotation. The study suggests that rotating the trunk when adopting a neutral spine inclined to 45° will maximise range of trunk rotation and encourage a natural stabilisation of the lower body. This posture meets the unique set of biomechanical requirements for the sport of golf and may help to reduce the risk of injury in manual material handling tasks. Conversely, rotating the trunk whilst the thoracolumbar spine is flexed leads to a reduction in trunk rotation ROM, encourages greater pelvic and lower body rotation, reduces torque production of the trunk and may increase the risk of lower back injury. These findings have important implications in relation to the teaching of spinal position during vocations, sports and activities of daily living that seek to maximise trunk rotation.
Keywords: Trunk rotation; Trunk inclination; Spine posture; Randomised repeated measures; Pelvic fixation; Range of motion ROM